A report on the state of agriculture and rural development in Latin america and the Caribbean - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
This document contains presentations made during a Round Table on the subject "Examination of the Status of Agriculture and Rural Development in Latin America and the Caribbean." This Round Table was organized by the Directorate of Analysis and Evaluation of the Inter-American Institute for Cooperation on Agriculture, and held on the final day of the Second Regular Meeting of the Inter-American Board of Agriculture, which took place in Kingston, Jamaica from October 24 through 28, 1983